A Task Force Against Local Inflammation and Cancer: Lymphocyte Trafficking to and Within the Skin - Lafouresse, Fanny; Groom, Joanna R. (Frontiers in Immunology, 2018)
The skin represents a specialised site for immune surveillance consisting of resident, inflammatory and memory populations of lymphocytes. The entry and retention of T cells, B cells and ILCs is tightly regulated to facilitate detection of pathogens, inflammation and tumours cells. Loss of individual or multiple populations in the skin may break tolerance or increase susceptibility to tumour growth and spread. Studies have significantly advanced our understanding of the role of skin T cells and ILCs at steady state and in inflammatory settings such as viral challenge, atopy and autoimmune inflammation. The knowledge raised by these studies can benefit to our understanding of immune cell trafficking in primary melanoma, shedding light on the mechanisms of tumour immune surveillance and to improve immunotherapy. This review will focus on the T cells, B cells and ILCs of the skin at steady state, in inflammatory context and in melanoma. In particular, we will detail the core chemokine and adhesion molecules that regulate cell trafficking to and within the skin, which may provide therapeutic avenues to promote tumour homing for a team of lymphocytes.